2015
DOI: 10.1002/chem.201500666
|View full text |Cite
|
Sign up to set email alerts
|

New Polyurethane/Docosane Microcapsules as Phase‐Change Materials for Thermal Energy Storage

Abstract: Polyurethane microcapsules were prepared by mini-emulsion interfacial polymerization for encapsulation of phase-change material (n-docosane) for energy storage. Three steps were followed with the aim to optimize synthesis conditions of the microcapsules. First, polyurethane microcapsules based on silicone oil core as an inert template with different silicone oil/poly(ethylene glycol)/4,4'-diphenylmethane diisocyanate wt % ratio were synthesized. The surface morphology of the capsules was analyzed by scanning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 23 publications
3
27
0
Order By: Relevance
“…Face‐centered orthorhombic phase appears as a sharp peak at 21.42° and the hexagonal packed phase appears at 21.80° as a small peak. It has been found that those rotators coexist with the triclinic phase during the cooling process when n ‐docosane is microencapsulated . Microcapsules of 2 μm size (Figure e) present the peaks already mentioned for the other sizes of microcapsules, but it is noticeable that for this size of capsule they appear as more defined peaks.…”
Section: Figurementioning
confidence: 59%
See 2 more Smart Citations
“…Face‐centered orthorhombic phase appears as a sharp peak at 21.42° and the hexagonal packed phase appears at 21.80° as a small peak. It has been found that those rotators coexist with the triclinic phase during the cooling process when n ‐docosane is microencapsulated . Microcapsules of 2 μm size (Figure e) present the peaks already mentioned for the other sizes of microcapsules, but it is noticeable that for this size of capsule they appear as more defined peaks.…”
Section: Figurementioning
confidence: 59%
“…FTIR spectra of the microencapsulated n ‐docosane (see Supporting Information, Figure S4) show the characteristic absorption bands for the polyurethane and for n ‐docosane, implying that the n ‐docosane has been successfully encapsulated into the PU shell.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Polyurethane microcapsules, a polyurethane product, are receiving increasing attention for their high thermal and mechanical stabilities, corrosion resistance, biocompatibility, and low cost. Due to these properties, polyurethane microcapsules have been widely applied in medicine, cosmetics, materials, and pesticides . Isocyanates, including toluene diisocyanate (TDI), methylene diphenyl isocyanate (MDI), and their modified derivatives, are common precursors for preparing polyurethane microcapsules.…”
Section: Introductionmentioning
confidence: 99%
“…Sixteen different fatty acids have been identified in mature stems of Agave plants, demonstrating the high potential of the genus as a candidate for fatty acid production in cell suspensions cultured in vitro. Among the n‐alkanes detected in the genus Agave is n‐docosane, a compound with many domestic and industrial applications in construction and in laboratories, and of high potential due to its energy storage capacity, lack of toxicity, non‐corrosive nature, low cost, and stability . Finally, the industrial wastes of Agave have been of interest for obtaining molecular hydrogen …”
Section: Biotechnological Advances In Agavementioning
confidence: 99%